2006
DOI: 10.1096/fj.05-4692com
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of melatonin against mitochondrial dysfunction associated with cardiac ischemiareperfusion: role of cardiolipin

Abstract: Reactive oxygen species (ROS) are considered an important factor in ischemia/reperfusion injury to cardiac myocytes. Mitochondrial respiration, mainly at the level of complex I and III, is an important source of ROS generation and hence a potential contributor of cardiac reperfusion injury. Appropriate antioxidant strategies could be particularly useful to limit this ROS generation and associated mitochondrial dysfunction. Melatonin has been shown to effectively protect against ischemic-reperfusion myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 58 publications
8
111
0
2
Order By: Relevance
“…Lipid peroxidation is a process whereby free radicals ''steal'' electrons from the lipids, resulting in cell damage and increased production of free radicals [33]. Recently, Majithiya and Balaraman [34] reported that metformin protects liver, kidney and aorta tissues against lipid peroxidation promoted by streptozotocin-induced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation is a process whereby free radicals ''steal'' electrons from the lipids, resulting in cell damage and increased production of free radicals [33]. Recently, Majithiya and Balaraman [34] reported that metformin protects liver, kidney and aorta tissues against lipid peroxidation promoted by streptozotocin-induced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…23 Mitochondrial ATP synthase activity was determined according to Yamada and Huzel 24 using the ATP Bioluminescence Assay Kit CLSII from Roche (Mannheim, Germany) as the ATP detection system. The respiratory control ratio was determined as described by Petrosillo et al 25 with a Clark-type oxygen electrode (H. Saur, Reutlingen, Germany) and succinate as the respiratory substrate.…”
Section: Determination Of Respiratory Chain Complex Activitiesmentioning
confidence: 99%
“…(32,33) Experimental data suggest that a high concentration of melatonin (40mg/L) confers anti-ischemic effects via its powerful antioxidant properties. (34,35) Our studies have shown that a low concentration of melatonin (corresponding to the concentration found in red wine), protects the heart against a lethal ischaemia-reperfusion injury in a rat model ( Figure 3). (36) Both melatonin and resveratrol confer cardioprotection via the activation of the recently discovered Survivor Activating Factor Enhancement (SAFE) pathway.…”
Section: Protective Wine Components: Resveratrol Melatoninmentioning
confidence: 98%